Influence of pre-strain on cryogenic tensile properties of 316LN austenitic stainless steel. (March 2020) - Zhang, Hengcheng; Huang, Chuanjun; Huang, Rongjin; Li, Laifeng
Highlights: The 0.2% proof stress and ultimate tensile strength at 4.2 K for 35% pre-strained specimens increased respectively around 86% and 18% compared to those of the as-received material. The elongation at fracture at both RT and 4.2 K decreased for the pre-strained 316LN SS compared to those of the as-received material. The pre-strained 316LN SS fractured at 4.2 K exhibits a ductile fracture mode. Abstract: In the present work, influences of room temperature tensile pre-strain on cryogenic tensile properties of 316LN austenitic stainless steel (SS) were investigated. The tensile properties of the 316LN SS with various tensile pre-straining amounts of 15%, 25% and 35% were measured at both room temperature (RT) and liquid helium temperature (4.2 K). Results indicated that both 0.2% proof strength ( Rp0.2 ) and ultimate tensile strength ( Rm ) at both RT and 4.2 K of the pre-strained 316LN SS significantly increased compared to those of the as-received material. The Rp0.2 and Rm at 4.2 K for 35% pre-strained specimens increased around 86% and 18%, respectively, compared to those of the as-received material. However, the elongation at fracture ( A ) at both RT and 4.2 K decreased for the pre-strained 316LN SS compared to those of the as-received material. The fractured morphologies of the pre-strained 316LN SS were investigated by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Dimples in the surface fractured at both RT and 4.2 K of the as-received and pre-strained 316LN exhibited a ductile fracture mode. Moreover, fractographic results indicated that the pre-strain treatment considerably decreased the ductility at both RT and 4.2 K. TEM analyses revealed that pre-strain treatment at RT led to dislocation accumulation and stress-induced martensite phase occurred at 4.2 K, which interpreted the cryogenic tensile properties of the pre-strained 316LN SS.